OP6 An investigation into suicide amongst ambulance service staff. Issue 1 (14th January 2019) - Hird, Kelly; Bell, Fiona; Mars, Becky; James, Catheryn; Gunnell, David
Abstract : Background: In 2015, Ambulance Service Medical Directors raised concerns regarding a perceived increase in suicide deaths among ambulance service staff. The Association of Ambulance Chief Executives (AACE) then commissioned a research study to investigate these concerns and provide recommendations towards a suicide prevention strategy. The aim of this study was to determine whether staff who work in the UK ambulance services (AS) are at higher risk of suicide than staff who work in other professions. Methods: Data was requested from the Office for National Statistics (ONS) regarding AS staff suicide. Eighteen AS were invited to return data on Occupational Health (OH). AS in England and Wales (n=11) were also asked to return data on staff suicides. Coroners were contacted to request permission to review the records of the deaths. Results: The ONS analysis of occupational suicide risk between 2011 and 2015 indicated that there were 20 suicide deaths amongst paramedics in England during that period. The risk of suicide amongst male paramedics was 75% higher than the national average. Over a 2 year period, 8 AS trusts identified 15 staff suicides (11 male, 4 female). The mean age of those dying by suicide was 42 years. Findings from coroners' records indicated that the predominant suicide method used was hanging (66.7%). Conclusions: The following recommendations have been accepted by the AACE: a) Develop a mental health strategy for all staff which includes specific emphasis on suicide prevention b) Review and assess suicide risk at times of increased vulnerability c) Collect and monitor data on AS suicides d) Review occupational health, counselling and support services e) Training for staff in identifying and responding to a colleague in distress f) Return to work discussions should consider and establish the status of an individual's mental health and wellbeing.